THE IMPORTANCE OF INDONESIAN LANGUAGE IN PUBLIC LIFE - Zahara Qifta; Doni pratama siregar; Rosnida (PT Rahis Cendekia Indonesia, 2024)
Television is one of the public media that fulfills many human needs and is very helpful in the need for educational knowledge. Television has three main functions, namely as follows. Firstly, television can provide accurate information and facts according to what is happening in the field. Both educational problems can also be seen to what extent they are. And thirdly as an entertainment medium. If one of them is not fulfilled then television will lose its social function in the eyes of society. Television as part of mass media is a transmission tool which also provides patterns and colors for the use of language, namely Indonesian and regional languages, as well as regional culture. Cultural diversity and development through mass media/television functions as mediating and shaping in shaping cultural discourse.